New product development in virtual environment - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2008)
Purpose - The literature on the topic has evolved exponentially since eight years ago. Relaying on a review of studies published in recent years, this article proposes and discusses a framework which incorporates a set of virtual teams involved in a new product development initiative.